The Impact of the Quality of Public Policies by Improving Morals and Ethics in Public Services for Bureaucratic Reform - Mubarok (International Journal of Science and Society, 2020)
In this reform era, public policy has become an essential matter for every citizen. Therefore, the government must be able to make public policies that are pro-society. Here the government is required not only to make right or wrong policies based on law but also to see the ethical and moral dimensions in society. An act that is law-abiding is not inherently moral and ethically correct. This study aims to clarify the importance of morality and ethics for decision-making officials by offering an overview of public policy ethics in Indonesia in general.